Impact of the Current Scenario and Future Perspectives for the Management of Oral Diseases: Remarkable Contribution of Herbs in Dentistry - Ahuja, Ashima; Singh, Sonia (Anti-Infective Agents, 2022)
Background: Herbs are the primary feedstock for treating numerous infectious diseases occurring in humans. The herb serves as a potential resource for managing dental disorders by maintaining oral hygiene and reducing the growth of microbes through the use of antimicrobial agents. The body-to-mouth connection helps essential facets that reduce the vulnerability of inflammation and infections in the mouth. The herbal product offers a better alternative for oral care than antibiotics due to reduced side effects and increased patient compliance. Herbs used in dentistry contain antimicrobial, antiseptic, anti-bacterial, anti-fungal, and antiviral properties that help in reducing irritation, infections, and pain in the oral cavity. The resistance to antibiotics and overcoming their untoward side effects promoted the usage of herbals in dentistry. In addition, due to the affordability issues of allopathic medicines in rural areas, the dependency of poor people on herbal medicines has gained significant popularity in the Indian subcontinent. Objective: Oral disorders would be a significant health setback for humankind due to their severity if they remained untreated. This review promotes the efforts made to overcome the side effects of allopathic medicines and provide cost-effective herbal treatment for oral care. Oral disorders cause various infections like tooth decay, dental caries, gingivitis, fungal, viral and bacterial infections, plaque formation, pemphigus vulgaris, pyorrhoea and mouth ulcers. The use of herbal extracts of tulsi, neem, and turmeric as a natural healer and the safest antimicrobial provides better dental care treatment. In addition, aromatic agents like tulsi, neem, mint, clove, ginger, and turmeric as dental products have increased palatability for patients who have lost their taste buds with growing age and diseases. Methods: The literature search was conducted through academics, Google scholar, PubMed, WHO, and Sci.org using keywords dentistry, antimicrobials, herbs for dental management, experimental findings, bacterial strains, oral health, and hygiene. Results: The beneficial results of using various antimicrobial-containing herbs are gaining popularity throughout the world. Subsequently, it has been further suggested that antimicrobials and herbal extracts maintain oral hygiene, reduce bacterial lichens and biofilm adhesion, help in the management of oral infections, and improve health. Conclusion: Screening of newer antimicrobial formulations like dentifrices, gargles, throat paints, mouthwashes, and mouth sprays containing cost-effective herbals for promoting healthcare plays a pivotal role in developing herbal industries for dental care.
Keywords: hygiene